If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -3 = 8x + -9 Reorder the terms: -3 + 13x = 8x + -9 Reorder the terms: -3 + 13x = -9 + 8x Solving -3 + 13x = -9 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -3 + 13x + -8x = -9 + 8x + -8x Combine like terms: 13x + -8x = 5x -3 + 5x = -9 + 8x + -8x Combine like terms: 8x + -8x = 0 -3 + 5x = -9 + 0 -3 + 5x = -9 Add '3' to each side of the equation. -3 + 3 + 5x = -9 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = -9 + 3 5x = -9 + 3 Combine like terms: -9 + 3 = -6 5x = -6 Divide each side by '5'. x = -1.2 Simplifying x = -1.2
| 2x+12=-12-4x | | 30=-(5-7x) | | 4+9x=-36+x | | 4+9x=-36-x | | c-5-c+3c+7= | | X^2-10z-2x=17 | | 5x(2x)=20 | | 3n+15=2n+20 | | 4x+8y=320 | | 7m+9=24 | | 2x-4-3x+3=0 | | 7x^2-80=0 | | -12m+18-30+5m= | | -6/5x=-4/3 | | 3x^4-2=0 | | 5(8)+15= | | 2.25+1=3.25+1.5x | | 2.5+1=3.25+1.5x | | 11-4(x+4)=13-6(x+2) | | -x+10y=-7 | | 7/5-3/4= | | 0.2x^2+2=0.6x^2 | | -9/4=1/3x | | 3/10y-2/5= | | 12y-48=4y | | 55+(6)= | | 0.5r^2-10=1.5r^2 | | 2y+49=9y | | 2[5+3(3+8)]= | | 4-2-12-5= | | 4n+20=2n+22 | | 18b^2-4b+27b-6= |